A review on utilization of plastic waste materials in bricks manufacturing process. (2021) - Kumar, Rishabh; Kumar, Mohit; Kumar, Inder; Srivastava, Deepa
Abstract: In present time due to urbanization the plastic utilisation in our daily life has been increased significantly as it being very useful and popular material. The only disadvantage is non-biodegradability. This study summarises the work done by authors to use plastic as construction material in bricks. The recyclable properties of plastic waste can be utilized to recycle this waste and produce a new product having lesser negative impact on the environment. One of the options to recycle plastic waste is to form bricks of plastic by mixing plastics with sand which can be used to replace traditional bricks. Various authors performed comparative study with brick made up of other materials by using various testing method such as scratch test, apparent porosity, water absorption, apparent porosity test, soundness test, efflorescence test and analysed that the further research on this field can enrich the strength, quality and durability of these masonry bricks. These bricks absorb very less water as compared to conventional bricks that is also very significant with the view of environmental sustainability.